Structural features of Ni-Cr-Si-B materials obtained by different technologies; IOP Conference Series: Materials Science and Engineering; Vol. 156 : Materials and Technologies of New Generations in Modern Materials Science - Kornienko E. E.; Nikulina A. A.; Belousova N. S.; Lazurenko D. V.; Ivashutenko A. S. Alexander Sergeevich; Kuzmin V. I. (2016, 2016)
Title screen